Study the relationship between the lifestyle of women and violence against them in series - abouzar kasemi; Ebrahim Mirzaei; Ali Ayar (توسعه اجتماعی, 2021)
Violence has historically been a nuisance to women. The intensity and rate of violence against women varies from region to region. The institutionalization of a patriarchal culture, the lack of adequate opportunities to demand women's rights, and socio-cultural poverty and financial dependence are involved. Accordingly, the main purpose of this study is to investigate the relationship between lifestyle and violence against women in Aleshtar. The research method is survey type and is quantitative in nature and applied in terms of purpose and has been implemented with a questionnaire. The statistical population of the studied women is equal to 4650 that 355 people have been selected as the sample through Cochran's formula and a questionnaire (and interview) has been distributed among them by random sampling method. Cronbach's alpha was used to determine the validity of the scales and experts and professors of social sciences were used to determine the reliability of the item. Disciplinary findings show that there is a significant and inverse relationship between violence against women between material consumption (-0.0332) and cultural consumption (-0.034). However, there was no relationship between leisure time and violence against women. In addition, there is a significant relationship between contextual variables of education level and employment status with violence against women. Accordingly, the results of multiple regression show that the coefficient of multiple correlation is equal to 0.519 and the coefficient of determination is equal to 0.324 that the sum of significant variables in the model have been able to explain and predict 0.32 of the variable of violence against women. Lifestyle gives women a fluid and floating position because it frees them from frozen class affiliations, empowers them to be more selective and creative, accelerates their material and productive participation, and gives them a new social identity of consumption, which This causes their position and subordinate role to diminish over time.